Acoustic Constraints and Musical Consequences: Exploring Composers' Use of Cues for Musical Emotion - Schutz, Michael (Frontiers in Psychology, 2017)
Emotional communication in music is based in part on the use of pitch and timing, two cues effective in emotional speech. Corpus analyses of natural speech illustrate that happy utterances tend to be higher and faster than sad. Although manipulations altering melodies show that passages altered to be higher and faster sound happier, corpus analyses of unaltered music paralleling those of natural speech have proven challenging. This partly reflects the importance of modality (i.e. major/minor), a powerful musical cue whose use is decidedly imbalanced in Western music. This imbalance poses challenges for creating musical corpora analogous to existing speech corpora for purposes of analyzing emotion. However a novel examination of music by Bach and Chopin balanced in modality illustrates that, consistent with predictions from speech, their major key (nominally ‘happy’) pieces are approximately a major second higher and 29% faster than their minor key pieces (Poon & Schutz, 2015, Frontiers). Although this provides useful evidence for parallels in use of emotional cues between these domains, it raises questions about how composers “trade-off” cue differentiation in music, suggesting interesting new potential research directions. This Focused Review places those results in a broader context, highlighting their connections with previous work on the natural use of cues for musical emotion. Together, these observational findings based on unaltered music—widely recognized for its artistic significance—complement previous experimental work systematically manipulating specific parameters. In doing so, they also provide a useful musical counterpart to fruitful studies of the acoustic cues for emotion found in natural speech.